Surface state selective tunable emission of graphene quantum dots exhibiting novel thermal quenching characteristics. (December 2018) - Dey, Tamal; Mukherjee, Subhrajit; Ghorai, Arup; Das, Soumen; Ray, Samit K.
Abstract: Highly luminescent, crystalline graphene quantum dots (GQDs) of homogenous size and shape with high yield have been successfully synthesized by a one-pot, facile and rapid synthesis technique. The characteristic blue emissions of GQDs from the crystalline sp 2 graphene core could be tuned from green to yellow wavelength, by modulating sp 3 -oxygeneous surface states. The progressive evolution of surface functional groups on annealing at different temperatures has been corroborated by X-ray photoelectron spectroscopy (XPS). Temperature dependent as well as excitation dependent photoluminescence (PL) behavior of the samples exhibits distinctly different thermal quenching characteristics. A transition from positive to negative thermal quenching phenomena with progressive annealing up to 300 ο C and crossovers at intermediate temperatures have been observed. With the help of schematic energy band diagram, we have explained the novel fluorescence mechanism in GQDs. Au/GQD/Au UV-photodetector device has been fabricated and its performance has been studied. Tunable emission of solution processed GQDs from UV to red wavelength can be very attractive for their use in bio-imaging and optoelectronics devices. Graphical abstract: Image 1